Galen's Viewpoint about Classification of Health States - Marzieh-Baygom Siahpoosh; Zahra-Baygom Siahpoosh (Tehran University of Medical Sciences, 2013)
Priority of health preservation and disease prevention to disease treatment is clear. During years, numerous studies with various aims have been done in relation with classification of health states based on some classification systems in order to determine level of healthiness among different groups of people. However it is thought that the need to classify interventions emerged for the first time in 1971, study of ancient medical sources results in getting some interesting things else. This study done through Qualitative research method on "Resale fi Hefzossehhat"authored by Galen, discusses about Galen's viewpoint about classification of health states.